Taksonomi dan Sejarah Penyebaran Ubijalar Sebagai Pangan Harapan Potensial (Taxonomy and History of Sweet Potato Distribution as Food Potential) - Yudi Widodo (Perum BULOG, 2013)
Kelangkaan pangan global kian menunjukkan akibat fatal dengan krisis komplek yang diiringi kelabilan politik dan memicu kerusuhan. Kasus Yunani, negara yang sejak kuno telah maju di semua bidang, termasuk filsafat ribuan tahun lalu, kini terpuruk ekonomi dan politiknya, sehingga warga negara terancam kekurangan pangan. Sementara itu, perubahan iklim global juga menjadi ancaman dalam peningkatan produktivitas, sehingga target untuk meningkatkan produksi pangan guna mengurangi kelaparan dan mengentaskan kemiskinan sesuai tujuan pembangunan milenium menjadi kecemasan baru. Eksploitasi jenis pangan yang didominasi oleh biji-bijian dan butir-butiran terutama serealia (padi, gandum, jagung dan Iain-Iain) dan leguminosa (kedelai, kacang tanah dan Iain-Iain) telah mencapai titik kejenuhan, sehingga sangat sulit untuk ditingkatkan potensinya. Ubijalar merupakan kelompok tanaman ubi-ubian yang potensinya menjadi harapan baru untuk memenuhi permintaan terhadap pangan. Meskipun kini telah dianggap sebagai pangan lokal, sebenarnya asal usul, sejarah penyebaran tanaman ubijalar perlu lebih diketahui agar mendapat pemahaman yang utuh.The taksonomical and historical distribution of sweet potato was discussed. The root crop is a potential food crop when the scarcity occurs. Food scarcity or food insecurity is the most important global issue affecting multidimensional crisis, includingpoliticalinstability in various countries. Recent situation in Greece, as an old developed country from the ancient, showed that her economic and political situations dropped into the worse circumstances, including malnutrition of the population. Moreover, the global climatic change is also threatening to the food production. So the target of the Millennium Development Goals through the increasing food production, reducing hunger and alleviating poverty encountered a new serious problem. So far, the exploitation of food crops is dominated from cereals and legumes such as rice, wheat, maize, soybean, peanut, mungbean etc, where theirproductivities revealed under saturation level, there by the endeavors to increase production are very difficult. Sweet potato as a food under tuberous rootcrop group therefore provides an alternative as the new potential food source to meet the greater demand forstaple food. Although sweet potato is considered to be local food, its real origin and historical distribution perspective as well as from taksonomicalpoint of view need to be understood holistically.